An Optimized Microwave-Assisted Extraction and Evaluation of Amino Acids Content and Nutritional Value in Chebulae fructus from Different Origins - Zhiqi Xu; Yan Li; Yuan Shen; Yiwu Wang; Jialing Yu; Xinxin Xiang; Lin Yang; Dan He (Foods)
The aim of this study is to establish a rapid and convenient microwave-assisted digestion method for sample pretreatment to evaluate amino acids in Chebulae fructus (CF). The microwave digestion method was optimized to extract amino acids from CF, and the differences in amino acids in CF from different origins and different processing states were analyzed and evaluated. The influences of digestion temperature, digestion time, and liquid–material ratio on extraction effect were investigated by sing factor test and response surface method (RSM), and the extraction conditions were optimized. The contents of 17 amino acids were determined by an automatic amino acid analyzer. The optimal digestion conditions were a digestion temperature of 150 °C, a digestion time of 18 min, and a liquid–material ratio of 65:1 (mL:g). Under these conditions, the total amino acid content of CF could reach 19.72 mg/g. CF from Lincang city of Yunnan province and unprocessed CF were considered to have higher nutritional value. The results of chemometric analysis showed that there were significant differences in the amino acid content in CF between Guangxi province, Dehong prefecture of Yunnan province, and Lincang city of Yunnan province, and six differential amino acids between the three origins were screened out. This study can provide references for the quality evaluation of the producing area, the extraction, and content research of amino acids of CF.